2013
DOI: 10.1590/s0004-27492013000100015
|View full text |Cite
|
Sign up to set email alerts
|

Essential trichomegaly: case report

Abstract: The present study reports two cases of symptomatic essential trichomegaly. Tri chomegaly may develop in various diseases, including anorexia nervosa, hypothyroidism, pregnancy, pretibial myxedema, systemic lupus erythematosus, vernal keratoconjunctivitis, and uveitis. The exact incidence trichomegaly is unknown, and the condition remains sporadically reported. Two cases of symptomatic trichomegaly without any associated systemic disorder are presented in this paper. Nazareth et al. (11) documented 23 medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Recent evidence suggested that Y174 is a highly conserved residue across species possessing critical roles in structure formation and functions of FGF5. The missense mutation of this residue into histidine (Y174H) may the underlying cause of trichomegaly, a disorder characterized by excessively long, pigmented, and thick eyelashes (Higgins et al, 2014; Rossetto et al, 2013). Y174 is characterized by its hydrophobic aromatic function group, whereas H174 is characterized by a positively charged imidazole functional group ( Figure 1A & B, top panels ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggested that Y174 is a highly conserved residue across species possessing critical roles in structure formation and functions of FGF5. The missense mutation of this residue into histidine (Y174H) may the underlying cause of trichomegaly, a disorder characterized by excessively long, pigmented, and thick eyelashes (Higgins et al, 2014; Rossetto et al, 2013). Y174 is characterized by its hydrophobic aromatic function group, whereas H174 is characterized by a positively charged imidazole functional group ( Figure 1A & B, top panels ).…”
Section: Introductionmentioning
confidence: 99%